VD_FINDINFO HC / 2011 / 181 vom 5. April 2011 - VD Tribunal cantonal (2011)
PROTECTION DE L'UNION CONJUGALE, DROIT DE GARDE, RELATIONS PERSONNELLES | 176 al. 3 CC, 308 al. 1 let. b CPC (CH), 312 al. 1 CPC (CH)